2003
DOI: 10.1109/titb.2003.821370
|View full text |Cite
|
Sign up to set email alerts
|

FAIR: a hardware architecture for real-time 3-D image registration

Abstract: Mutual information-based image registration, shown to be effective in registering a range of medical images, is a computationally expensive process, with a typical execution time on the order of minutes on a modern single-processor computer. Accelerated execution of this process promises to enhance efficiency and therefore promote routine use of image registration clinically. This paper presents details of a hardware architecture for real-time three-dimensional (3-D) image registration. Real-time performance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 27 publications
0
46
0
Order By: Relevance
“…There are several techniques developed using parallel computing [17][18][19][20][21]for fastest Image Registration has been developed. Some of them are "A Parallel GPU Algorithm for Mutual Information based 3D Non rigid Image Registration" [22], "A Parallel Mutual Information Based Image Registration Algorithm for Applications in Remote Sensing" [23], "GPU Accelerated Medical Image Registration Techniques" [24], "Acceleration of Genetic Algorithm with Parallel Processing with Application in Medical Image Registration" [25], "Parallel Image Registration Using Bio-Inspired Computing" [26], "Multimodal Image Registration Using GPU Parallel Computing Technology" [27], "Fast Parallel Image Registration On CPU And GPU For Diagnostic Classification Of Alzheimer's Disease" [28], "Histogram-Based Image Registration Using Parallel Computing" [29].…”
Section: Mutual Informationmentioning
confidence: 99%
“…There are several techniques developed using parallel computing [17][18][19][20][21]for fastest Image Registration has been developed. Some of them are "A Parallel GPU Algorithm for Mutual Information based 3D Non rigid Image Registration" [22], "A Parallel Mutual Information Based Image Registration Algorithm for Applications in Remote Sensing" [23], "GPU Accelerated Medical Image Registration Techniques" [24], "Acceleration of Genetic Algorithm with Parallel Processing with Application in Medical Image Registration" [25], "Parallel Image Registration Using Bio-Inspired Computing" [26], "Multimodal Image Registration Using GPU Parallel Computing Technology" [27], "Fast Parallel Image Registration On CPU And GPU For Diagnostic Classification Of Alzheimer's Disease" [28], "Histogram-Based Image Registration Using Parallel Computing" [29].…”
Section: Mutual Informationmentioning
confidence: 99%
“…Fast automatic image registration (FAIR) [4] is such an architecture proposed by Castro-Pareja et al for accelerated hardware implementation of rigid image registration. FAIR is optimized and fine tuned for partial-volumeinterpolation-based image registration by means of pipelining, parallel memory access, and distributed processing.…”
Section: Fpga Technologymentioning
confidence: 99%
“…Speedup of registration is achieved by identifying throughput bottle neck areas and optimizing them in order to decrease the processing time. Speedup of the algorithm can be obtained by using pipelined architectures and also by using parallel architectures [4]. Since the majority of the registration execution time is spent on calculating the mutual histogram, accelerating mutual histogram calculation has been the focus of our work.…”
Section: Computation Of Mutual Informationmentioning
confidence: 99%
“…Memory organization and neighborhood access techniques are often the limiting factors in 3D image processing systems [139][140][141][142]. However, most practical filtering techniques employ standard neighborhood operations that require block- begins.…”
Section: Memory Controller and Brick-caching Schemementioning
confidence: 99%
“…Castro-Pareja et al [139] have shown that, for typical medical images, accumulating In general, the execution time T required by a pipelined implementation (with n-stages) of an operation is given as:…”
Section: Acceleration Approachmentioning
confidence: 99%